MALIC DEHYDROGENASE ACTIVITY AT 101 C UNDER HYDROSTATIC PRESSURE - Morita, Richard Y. (1962)
Morita, Richard Y. (University of Nebraska, Lincoln) and Roger D. Haight. Malic dehydrogenase activity at 101 C under hydrostatic pressure. J. Bacteriol. 83:1341–1346. 1962.—No malic dehydrogenase activity was found to occur at 101 C at various hydrostatic pressures from 1 to 700 atm. However, activity was demonstrated with hydrostatic pressures above 700 atm, with optimal activity at 1,300 atm at the same temperature. Explanation of the data is based upon thermal denaturation of the enzyme, which involves a molecular volume increase of the enzyme. The molecular volume increase is counteracted by hydrostatic pressure. Pressures above 700 atm to 1,500 atm (highest employed) were sufficient to offset the denaturation by 101 C which probably resulted in an incomplete denaturation of malic dehydrogenase.